A cross-sectional study of knowledge, attitude and practices on HIV/AIDS among nursing students at a tertiary care centre, Hyderabad, India - Allenki, Vineesh; Pokkuluri, Abhishek; Chajhlana, Sunil Pal Singh (International Journal Of Community Medicine And Public Health, 2022)
Background: Acquired immunodeficiency syndrome (AIDS) caused by human immunodeficiency virus (HIV) infection is a dreadful condition to treat. Knowledge, attitude and practice (KAP) towards the people living with HIV (PLHIV) has a pivotal role in preventing further progression of the disease. Nurse’s role in these aspects is essential because, the little knowledge, inappropriate attitude and inadequate practices towards PLHIV will hinder the delivery of services. Special nursing knowledge and expertise are required to care for these patients and the present study aimed to address this issue. Methods: A cross-sectional study of KAP on HIV/AIDS was conducted between January 2022 and February 2022 among nursing college students at a tertiary care centre using a standard questionnaire. Data collected was entered and analysed with MS excel 2013 and Epi info 7.2.5 and represented in form of tables. Results: Overall knowledge of the nursing students was good. There were few drawbacks in the perceived knowledge that majority of students believed that gloves and gowns are required for any contact with patients with HIV/AIDS (59.0%). Most students believed that patients living with HIV/AIDS have the right to the same quality of care as any other patient. (53.9%). Around 95.0% of the students practiced washing hands before examining patients. Conclusions: Training regarding HIV/AIDS for nursing students is a critical aspect in boosting understanding, correcting misconceptions, fostering a positive attitude, and improving compliance with universal precautions and other preventative behaviors. It also helps to deliver effective and appropriate care to PLHIV while protecting themselves from infection.